2014
DOI: 10.1161/hypertensionaha.114.03261
|View full text |Cite
|
Sign up to set email alerts
|

Increased Reactive Oxygen Species, Metabolic Maladaptation, and Autophagy Contribute to Pulmonary Arterial Hypertension–Induced Ventricular Hypertrophy and Diastolic Heart Failure

Abstract: Pulmonary arterial hypertension (PAH) is a debilitating and deadly disease with no known cure. Heart failure is a major comorbidity and a common cause of the premature death of patients with PAH. Increased asymmetrical right ventricular hypertrophy and septal wall thickening compress the left ventricular cavity and elicit diastolic heart failure. In this study, we used the Sugen5416/hypoxia/normoxia-induced PAH rat to determine whether altered pyridine nucleotide signaling in the failing heart contributes to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 58 publications
4
48
0
1
Order By: Relevance
“…RVSP in the control and PAH rats was positively correlated with the respective RV/LVϩS. Consistent with our previous studies (2,49), the PAH rats were not in dilated cardiomyopathy stage at either 8 or 13 wk.…”
Section: Rvsp and Rv/lvϩs Are Increased In Pah Ratssupporting
confidence: 91%
See 2 more Smart Citations
“…RVSP in the control and PAH rats was positively correlated with the respective RV/LVϩS. Consistent with our previous studies (2,49), the PAH rats were not in dilated cardiomyopathy stage at either 8 or 13 wk.…”
Section: Rvsp and Rv/lvϩs Are Increased In Pah Ratssupporting
confidence: 91%
“…Consistently, studies show that miR-140 plays a role in promoting cardiomyocyte apoptosis by suppressing the expression of MFN1, and knockdown of miR-140 reduces myocardial infarct size (35). Previously, others and we have shown that apoptosis and autophagy/mitophagy are increased in the RV of PAH rats (2,49) and of mice with pulmonary artery banding (48), suggesting a decline of myocardial function. Mitochondria constantly undergo fusion and fission to maintain organelle homeostasis (28,30), and abnormality in this phenomenon triggers apoptotic cell death (47).…”
Section: H693supporting
confidence: 78%
See 1 more Smart Citation
“…Second, while we demonstrate favorable effects of endogenous or exogenous E 2 on proapoptotic signaling, eNOS phosphorylation, and autophagic flux, these parameters were not significantly affected by SuHx or sex. While this may suggest that these pathways do not play a role in RV failure, this is unlikely in light of previously published data that demonstrate pathophysiological relevance (6,14,29,46,47,52). A more likely explanation is that the present studies were underpowered to detect more profound changes in these endpoints.…”
Section: Discussionmentioning
confidence: 71%
“…G6PD inhibition relaxes pulmonary arteries by decreasing intracellular calcium (20), prevents switching of vascular smooth muscle cells to a synthetic phenotype (9,10), and reduces pulmonary hypertension (9,47). However, whether prolonged hypoxia-induced 20-HETE-synthesis is G6PD dependent or independent and whether G6PD modulates 20-HETE signaling in the vascular smooth muscle remain unknown.…”
Section: -Hydroxyeicosatetraeonic Acid (20-hete) Plays a Critical Rmentioning
confidence: 99%